(untitled) (Research, Society and Development, 2020)
Manguita is a fruit understudied, common in the Northeast region of Brazil, which stands out for its sweet taste and slightly acid in addition to the pleasant aroma. The objective of this study was to evaluate the postharvest quality of mango var. Manguita stored at room temperature for 10 days. The fruits were obtained in Limoeiro do Norte, Ceará. The physical, physical-chemical, centesimal, antioxidant activity and bioactive characteristics were evaluated. The results were analyzed by means of regression, analysis of variance and the comparison of means by Tukey. The Manguitawas characterized as a small, rounded fruit with a high pulp content, with acid character and considerable availability of nutrients, among them sugars, vitamin C and bioactive compounds. Storage at room temperature did not influence the external or internal appearance until the eighth day of storage.